2019
DOI: 10.1186/s12871-019-0819-2
|View full text |Cite
|
Sign up to set email alerts
|

Emergence delirium in children is not related to intraoperative burst suppression – prospective, observational electrography study

Abstract: Background Emergence-delirium is the most frequent brain dysfunction in children recovering from general anaesthesia, though the pathophysiological background remains unclear. The presented study analysed an association between emergence delirium and intraoperative Burst Suppression activity in the electroencephalogram, a period of very deep hypnosis during general anaesthesia. Methods In this prospective, observational cohort study at the Charité - university hospital … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 23 publications
1
15
1
Order By: Relevance
“…In this pilot study, burst suppression events occurred in 56% of children 1–36 months of age undergoing surgery using sevoflurane or propofol and remifentanil infusion maintenance anesthesia. The prevalence was similar to data reported by Koch et al, 15 who observed that 52% of children had burst suppression during general anesthesia. We demonstrated a significant difference in the prevalence of burst suppression between sevoflurane and propofol anesthesia (72% vs .…”
Section: Discussionsupporting
confidence: 91%
“…In this pilot study, burst suppression events occurred in 56% of children 1–36 months of age undergoing surgery using sevoflurane or propofol and remifentanil infusion maintenance anesthesia. The prevalence was similar to data reported by Koch et al, 15 who observed that 52% of children had burst suppression during general anesthesia. We demonstrated a significant difference in the prevalence of burst suppression between sevoflurane and propofol anesthesia (72% vs .…”
Section: Discussionsupporting
confidence: 91%
“…These distinct receptor affinities of the different anesthetic agents are most likely the underlying causes for their different EEG signatures ( Purdon et al, 2015b ) and their different ability to induce burst suppression activity ( Purdon et al, 2015a ). Since in preschool children, elevated neuronal excitability is related to the occurrence of emergence delirium ( Martin et al, 2014 ; Koch et al, 2018 ), but not the presence of burst suppression activity ( Faulk et al, 2010 ; Frederick et al, 2016 ; Koch et al, 2019 ), it is obvious, that there are different pathophysiological neuronal states being related to delirious symptoms. Moreover, it has been shown in molecular studies that volatile anesthetics can mediate inflammatory responses or may show neurotoxic effects ( Jiang and Jiang, 2015 ; Yuki and Eckenhoff, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of burst suppression during sedation has been shown to correlate with delirium risk, prolonged hospital stay, cognitive impairment after treatment, and increased mortality in adults [40]. Recent studies investigating risk factors for emergence delirium in pediatric patients could not confirm a relationship between intra-operative burst suppression and post-operative delirium [41]. However, studies regarding the effects of deep sedation in intensive care patients are lacking.…”
Section: Discussionmentioning
confidence: 99%